Effectiveness of ecological laboratory work in the teaching of physics in connection with labor education - Dusyarov Xudoymurod Chorshanbiyevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article aims to conduct environmental education through interdisciplinary